BREAKING BAD NEWS - PERCEPTIONS OF CANCER PATIENTS AND THEIR RELATIVES - Jameel, Abid; Farooq, Muntajeeb; Ullah, Salim (Journal of Postgraduate Medical Institute, 2011)
Objective: To study the perceptions of cancer patients and their relatives regarding disclosure of cancer Methodology: A cross sectional survey was conducted at Medical Oncology Ward, Hayatabad Medical Complex, Peshawar from September 2009 to January 2011. A total of 114 patients and their relatives were interviewed using a pre-designed questionnaire. Results: Eighty Three (73%) were male while 31 (27%) were female. Median age of cancer patients was 36 (18-70) years. Forty-eight percent (29/60) cancer patients wished for full disclosure of bad news while 39% (21/54) of their relatives wanted full disclosure (p= Not Significant). Sixty two percent (37/60) cancer patients and 74% (40/54) relatives wanted to be informed in case of recurrence (p= Not Significant). Over 90% of patients and relatives wanted bad news to be broken by a senior consultant. Fifty eight percent (35/60) cancer patients and 52% (28/54) relatives wished for their relatives to make treatment decisions for them (p= Not Significant). However, 93% (56/60) of cancer patients and 78% (42/54) of their relatives wanted full information about all side-effects of treatment (p < 0.02). Fifty eight percent (35/60) cancer patients and 32% (17/54) relatives wanted their close relatives to be present while bad news was being broken (p<0.007). Conclusion: Almost half of patients wished for full disclosure of information regarding cancer diagnosis. Over 90% patients wanted full information regarding all side-effects of chemotherapy. It is recommended that training regarding how to break bad news be made mandatory part of our medical training both at undergraduate and postgraduate levels. related information.